Identification of Informal Reasoning Patterns of Biology Prospective Teachers Based on Socio-scientific Issues (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2023)
This research was conducted to overcome the lack of integration of socio-scientific issues (SSI) at the Mandalika University of Education, especially the biology education department, and at the same time as a springboard for developing teaching programs. This basic qualitative research aims to identify and explain informal reasoning patterns of biology prospective teachers. In this study, 14 biology prospective teachers as samples were selected purposively, namely students who had taken animal physiology, genetics, and evolution courses. Furthermore, semi-structured interviews using thematic techniques focused on issues of common descent, GMOs, and organ transplants. The findings and conclusions of this study indicate that intuitive and emotive reasoning is the reasoning patterns most used by our respondents in responding to SSI issues. Then, for further research, it is stated briefly in the recommendations section.